Brand Loyalty in the Malaysian Banking Sector - Mohammad Naim, Ismail (2009)
This research explores the factors that contribute to brand loyalty in the Malaysian banking sector. A field survey of bank customers that visited banks around Kangar, capital of Perlis, was conducted to determine the significance and influence of the dimensions such as satisfaction, communication, trust, image and perceived quality on brand loyalty in the Malaysian banking sector. A total of 500 questionnaires were distributed to ten participating banks through systematic quasi-random sampling, 438 questionnaires were obtained and usable. Pearson correlation test showed that 'perceived quality' is the most significant towards brand loyalty, followed by 'image', 'communication', 'trust' and 'satisfaction'. On the other hand, regression analysis indicated that perceived quality, image, satisfaction and communication were factors that influence brand loyalty, while trust was not influencing respondents towards brand loyalty. Therefore, banks need to give quality services perceived by their customers, build and sustain a positive brand image, should be trustworthy and committed to the service ethics, should communicate timely and accurately, and make their customers satisfy with services given.